Perspectives and practices of nutritionists on dietary supplements for elite soccer teams: a cross-sectional survey study - Abreu, R.; Oliveira, C. B.; Brito, J.; Teixeira, V. H. (Frontiers in Sports and Active Living, 2023)
Introduction and objectives: Dietary supplements are part of the nutritional strategies frequently applied in sports performance support. With growing research on this subject and high demand from athletes, nutritionists need to keep up to date with the latest evidence and utility of dietary supplements, particularly in real-world contexts. As information about the use of dietary supplements among elite soccer players is still scarce, this work aimed to know how nutritionists working with elite soccer teams perceive and use these substances in their daily practice.